Null Controllability of a Four Stage and Age-Structured Population Dynamics Model - Amidou Traoré; Bedr’Eddine Ainseba; Oumar Traoré (Journal of Mathematics)
This paper is devoted to study the null controllability properties of a population dynamics model with age structuring and nonlocal boundary conditions. More precisely, we consider a four-stage model with a second derivative with respect to the age variable. The null controllability is related to the extinction of eggs, larvae, and female population. Thus, we estimate a time T to bring eggs, larvae, and female subpopulation density to zero. Our method combines fixed point theorem and Carleman estimate. We end this work with numerical illustrations.